Dirty rotten scoundrels [videorecording (Blu-Ray)] - Launer, Dale; Shapiro, Stanley; Henning, Paul, 1911-2005; Martin, Steve, 1945-; Caine, Michael; Headly, Glenne; Rodgers, Anton, 1933-2007; Harris, Barbara, 1935-2018; McDiarmid, Ian; Ivey, Dana; Fay, Meagan; Conroy, Frances (Shout select, 2019)
In the south of France, two rival con men, suave and sophisticated Lawrence and third-rate American hustler Freddy, make a wager. The first one to extract $50,000 from the next woman they meet wins, and the other leaves town.